Effect of topical ginger on the pain of venipuncture in hemodialysis patients: A randomized controlled trial - Bita Koushki; Hossein Ebrahimi; Seyedeh Solmaz Talebi; Nasrin Fadaee Aghdam; Mahboobeh Khajeh (Tehran University of Medical Sciences, 2021)
Background & Aim: Pain during vascular access is an integral part of the life of hemodialysis patients. The aim of this study was to determine the effect of topical ginger on pain following needle insertion into the arteriovenous fistula in hemodialysis patients. Methods & Materials: In this clinical trial, 100 hemodialysis patients were selected from two hospitals in Shahroud in 2019 and were randomly assigned to intervention or control groups. For the intervention group, ginger ointment was used 20 minutes before needle insertion into the arteriovenous fistula. The control group only received routine care. Patients' pain after needle insertion was assessed using the Numerical Pain Rating Scale. Data was analyzed using the SPSS software version 18 and Chi-square, Fisher, and independent t-tests. Results: There was a statistically significant difference in the mean and standard deviation of pain scores between the control (8.46±1.26) and intervention (5.08±1.29) groups (P<0.001). While most people in the intervention group experienced moderate pain, most people in the control group had severe pain. Conclusion: According to the results of the study, the use of topical ginger, which is cheap with almost no side effects, can reduce the severity of pain following needle insertion into the arteriovenous fistula in hemodialysis patients, and its use in hemodialysis wards is recommended. Clinical trial registry: IRCT20190825044608N1